A thienothiophene and anthracene based functional hyperbranched polymer: synthesis, photophysical properties and photocatalytic studies - İşçi, Recep; Bildirir, Hakan; Gunturkun, Dilara; Gomez-Mendoza, Miguel; Liras, Marta; O’Shea, Victor A. de la Peña; Öztürk, Turan (Royal Society of Chemistry, 2024)
Conjugated polymer photocatalysts have been receiving extensive attention in the field of photocatalytic hydrogen evolution, owing to their tunable molecular structures and electronic properties. Herein, we report a hyperbranched conjugated polymer, containing thienothiophene and anthracene units (TT-Ant), synthesized via Pd(0) catalyzed Suzuki coupling. Its structural, photophysical and electrochemical features were investigated by using UV-vis and fluorescence spectroscopy, cyclic voltammetry (CV) and X-ray photoelectron spectroscopy (XPS). Photocatalytic hydrogen evolution tests, combining the material with two different additives, resulted in high hydrogen production rates from water. A steady state production rate of around 286 μmol g−1 h−1 for its hybridization with TiO2 was recorded, which is more than 3 times that for pristine TiO2 under the same conditions. Moreover, the combination of the polymeric material with platinum (1% wt) resulted in a maximum rate value of 700 μmol g−1 h−1. The surface properties of the latter combination before and after the reaction were studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), which demonstrated successful Pt deposition on the surface of the polymer. This work may provide a new strategy to construct stable photocatalysts with thienothiophene and anthracene cores as active sites for efficient catalytic reactions in energy conversion applications.
Keywords: conjugated polymers; photocatalysts; conjugated polymer photocatalysts; functional hyperbranched polymers